2021
DOI: 10.1097/bth.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Cosmetic Reconstruction of Floating Thumb: A Thumb-preserving Technique

Abstract: FIGURE 3. Initial radiograph of the hypoplastic thumb (A), and postoperative radiograph (B).FIGURE 4. Postoperative radiograph of the foot after harvesting the fourth metatarsal bone (A), and postoperative radiograph 6 months after surgery (B).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Beyond the evident aesthetic concerns, these anomalies significantly impact hand function and overall limb dexterity. Conventional reconstructive methods have centered around metacarpal augmentation, tendon transfers, and soft tissue reconstruction [13,14]. In a previous study, Liu et al focused specifically on surgical reconstruction for the more severe type IIIB and IV cases using a non-vascularized fourth metatarsal bone graft, which achieved reasonable hand function and cosmesis in 16 patients with 17 type IIIB and IV hypoplastic thumbs over 46 months, despite 2 nonunions [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the evident aesthetic concerns, these anomalies significantly impact hand function and overall limb dexterity. Conventional reconstructive methods have centered around metacarpal augmentation, tendon transfers, and soft tissue reconstruction [13,14]. In a previous study, Liu et al focused specifically on surgical reconstruction for the more severe type IIIB and IV cases using a non-vascularized fourth metatarsal bone graft, which achieved reasonable hand function and cosmesis in 16 patients with 17 type IIIB and IV hypoplastic thumbs over 46 months, despite 2 nonunions [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, these approaches can be limited in cases with severe deficiency, demanding alternative strategies to achieve optimal outcomes. For instance, Takagi et al reported that pollicization of the index finger offers a solution for severely floating thumbs, allowing retention of 5 digits while improving function under the presence of the available fingers in the donor area [13]. Furthermore, proper care, planning, technique selection, adjunct procedures, and rehabilitation are essential for optimal functional results [16].…”
Section: Introductionmentioning
confidence: 99%